Effect of Butorphanol with and without Medetomidine on Intraocular Pressure in Cats - Mohammadi, N; Yanmaz, LE (Journal of the Hellenic Veterinary Medical Society, 2023)
This study aimed to determine the effects of intramuscular administration of butorphanol with and without medetomidine on intraocular pressure (IOP) in cats. Sixteen clinically normal cats were used. Cats were randomly received two-treatment regimen. The first regimen was 0.2mg/kg butorphanol, and the second regimen was a mixture of 0.1mg/kg butorphanol and 0.05mg/kg medetomidine. IOP values were recorded before treatment (T0) and following the treatment at 10 (T10), 20 (T20), 30 (T30), and 40 min (T40) in both groups. Administration of butorphanol with and without medetomidine did not cause a statistically significant change in IOP values. The IOP did not change over time (p = 0.41). The mean values of IOP in butorphanol, and butorphanol-medetomidine groups were 20.00 ± 2.29 and 20.38 ± 2.35 mm Hg, respectively. In conclusion, intramuscular administration of butorphanol with or without medetomidine had no significant effect on IOP in cats.